On commuting symmetric operators - Zagorodnyuk, S. M. (Methods of Functional Analysis and Topology, 2012)
In this paper we present some conditions for a pair of commuting symmetric operators with a joint invariant dense domain in a Hilbert space, to have a commuting self-adjoint extension in the same space. The remarkable Godic-Lucenko theorem allows to get a convenient description of all such extensions.